Ocena poziomu zrównoważonego rozwoju krajów Europy Środkowej i Wschodniej na tle UE-27 – wielowymiarowa analiza porównawcza - Stec, Małgorzata; Grzebyk, Mariola (Przegląd Wschodnioeuropejski, 2024)
The paper presents a multidimensional comparative analysis of the level of sustainable development of Central and Eastern European countries that are EU members. The research was based on the Eurostat database for 2020, including a set of 22 variables determining the social, economic and environmental dimensions of sustainable development. The research method used was the zero unitarization method. The results of the research conducted confirm that in 2020 the countries of Central and Eastern Europe were diversified not only in terms of the general level of sustainable development, but also in its individual dimensions. Among the countries of Central and Eastern Europe, Slovenia, Estonia and Poland had the best situation in terms of the overall level of sustainable development. On the other hand, Lithuania, Bulgaria and Romania, had the worst. The research also confirmed that the strongest side of the surveyed countries was the environmental dimension of sustainable development.